Aflatoxins occurrence through the food chain in Costa Rica: Applying the One Health approach to mycotoxin surveillance - Granados Chinchilla, Fabio (2017)
Aflatoxins (AFs) are toxic metabolites produced by Aspergillus spp. and commonly found in crops, grains, feedstuff, and forages. Exposure to AFs has been associated with increased risk of liver cancer and growth retardation in humans, liver damage, immunosuppression, embryotoxicity in both animals and humans, and decreased milk, egg and meat production in animals. For the first time, the Costa Rican national mycotoxin surveillance programs for animal feed and food are considered as a whole, applying the One Health approach to the mycotoxin epidemiological research. Therefore, the aim of this study was to determine the occurrence of AFs in cereals, nuts, grains intended for animal and human consumption in Costa Rica. In animal feed and feed ingredients, 970 samples were analyzed for AFs from 2010 to 2016 with an overall prevalence of positive samples of 24.0% (ranging from 0.01 to 290 μg kg−1). Only 2.5% of the samples failed to comply the regulation for total AFs (20 μg kg−1 feed). From 5493 samples of agricultural commodities intended for human consumption analyzed from 2003 to 2015, there was an overall prevalence of AF positive samples of 10.8% (ranging from 0.48 to 500 μg kg−1), and 2.8% did not comply the regulation for AFs (20 μg kg−1). In both feed and food, the highest AF prevalence corresponded to corn ingredients (27.8%) and white corn (38.6%), respectively. Among the commodities intended for human consumption, red beans had the highest aflatoxin concentrations (500 μg kg−1).